Filmowe dybuki: od żydowskiej legendy do polskiego koszmaru sennego - Nowakowski, Jacek (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article discusses several screen adaptations of the drama Dybbuk or Between Two Worlds by Szymon An-ski. Written on the basis of an old Jewish legend, An-ski’s play has provided inspiration for many movies. The four analysed works represent different cultural traditions and film genres and come from different decades of the cinema history. Diverse as they are, these four works emphasize different issues. They are: Dybbuk by M. Waszyński – the best Polish movie in Yiddish exploring the Jewish folklore; A Serious Man by the Coen brothers, with a ‘dybbuk’ prologue that redefines their art towards the Judaic tradition, as well as two other works that are strongly characteristic of the film genres that they represent: The Possession by O. Bornedal, using the poetics of religious horror, and the Polish thriller The Demon by M. Wrona, drawing from the tradition of the national drama as defined by Wesele [The Wedding ] by S. Wyspiański and its screen adaptations and travestations.